Attitudes Towards the Elderly Among Students of Pedagogy - Katarzyna Jas (Ignatianum University Press, 2021)
The main aim of this study is to consider and present pedagogy students' attitudes towards the elderly. The results presented herein were collected in a pilot project. The survey was conducted among 66 pedagogy students; a questionnaire and the semantic differential method were used as the research tools. The results revealed positive attitudes among the students towards the elderly. However, a conclusion was drawn that pedagogy students should be allowed to take part in activities involving the elderly. Students's awareness of their own attitudes might allow them to understand elderly people's behavior. A proper understanding of the aging process and old age can create a chance for better communication and inter-generational cooperation. It is also an inspiration for understanding their own aging process.